Organizing a Set of Empirical Findings on the Causes and Effects of Technical Debt through a Globally Distributed Family of Surveys: Extended Abstract - Rios, Nicolli; Spínola, Rodrigo; Mendonça, Manoel (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2021)
The concept of technical debt (TD) contextualizes the problem of outstanding development tasks as a type of debt that brings a short-term benefit to the project, but may have to be paid with interest later on the development process. It is common for a software project to incur debt during the development process, however, its presence brings risks to the project and makes it difficult to manage. This Thesis investigates, through continuous and independent replication of globally distributed surveys, the state of the practice on TD including causes that lead to its occurrence, its effects, and how TD manifest itself in software projects. Responses from 432 professionals from Brazil, Chile, Colombia, and the United States were analyzed. The main causes and effects of TD, and the relationship between process models and the TD effects were identified. Besides, probabilistic cause and effect diagrams and a conceptual map focused on documentation debt were proposed to support TD management. Also, this Thesis established a cooperation network involving researchers from 12 countries in the field of TD, through the InsighTD project, the first large-scale study in the area.